Judge's Consideration of the Application for Making a Death Certificate at the Tanjung Karang District Court in 2023 - Wardhana, Rian Prasetyo; Baharudin, Baharudin; Alfiyan, Angga (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This writing discusses the importance of recording death certificates in society, focusing on the judge's considerations regarding the application for the creation of death certificates at the Tanjung Karang District Court in 2023. The human life cycle involves various significant events, including death, which requires documentation for legal certainty and administration. Despite existing regulations, there is still a lack of public interest in handling death certificates. Factors influencing people's reasons for obtaining death certificates involve legal obligations, inheritance administration, insurance claims, legal security, retirement, identity control, civil registry updates, religious rituals, asset management, and social assistance. This research employs a normative legal research method, referencing Law Number 16 of 2019 and Law Number 1 of 1974. The results indicate that the judge's considerations in approving or rejecting applications for death certificate issuance include sufficient evidence, public interest, procedural accuracy, data consistency, suspicion of information, disagreements among parties, the legal validity of applicants, the interests of children or heirs, and the risk of misuse. Understanding these factors is crucial in comprehending and raising public awareness about the importance of death certificate recording.